PEMBERDAYAAN PAGUYUBAN PENGRAJIN BATIK DS. SIJAMBE WONOKERTO MELALUI PAKET KESELAMATAN KERJA - Eko Budi Prasetyo; Nonik Eka Martyastuti; Maghfiroh Maghfiroh (LPPM Universitas Pekalongan, 2022)
A safe and comfortable work environment is very much needed for workers, including batik industry in Sijambe, Wonokerto, Pekalongan. This relates to the use of Personal Protective Equipment at work, work position, duration of work and conditions of the work environment. When conducting direct interviews with batik craftsmen, the following data were obtained, 50% of batik craftsmen felt pain in the buttocks, right knee, left leg; 60% pain in the upper neck, waist, left forearm, left knee; 70% feel pain in the lower neck, back and buttocks. Judging from the position of the equipment used, it can be seen that the working position of batik is not comfortable. The lighting used by batik craftsmen uses lamp lighting and ventilation that do not meet good lighting standards. The temperature at the time of observation reached 28-29oC with a humidity of 71%. This temperature makes the area of the batik maker quite hot, this temperature cannot be said to be comfortable for activities because a good temperature for workers ranges from 18.3-21.3oC, while the relative humidity in one room should be between 40-60% in summer, which is the relative humidity that gives a comfortable atmosphere in the room. Based on the analysis of the situation and problems, education about types, containers, places, labeling, hazard effects, and environmental impacts is needed. Education related to the use of Personal Protective Equipment at work to avoid work accidents. In addition, there is a need for health education about occupational diseases that are risky for Batik Craftsmen. Physical examination of batik craftsmen is needed to determine the health status of the craftsmen and as a basis for providing physiotherapy interventions for massage and irradiation using Infra Red. Keywords : Batik, Personal Protective Equipment, health